2022
DOI: 10.3389/fonc.2022.918778
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 in Cancers: Bidirectional Function, Drug Resistance, and Regulatory Mechanism

Abstract: Aldehyde dehydrogenases 1 family member A1(ALDH1A1) gene codes a cytoplasmic enzyme and shows vital physiological and pathophysiological functions in many areas. ALDH1A1 plays important roles in various diseases, especially in cancers. We reviewed and summarized representative correlative studies and found that ALDH1A1 could induce cancers via the maintenance of cancer stem cell properties, modification of metabolism, promotion of DNA repair. ALDH1A1 expression is regulated by several epigenetic processes. ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 98 publications
(132 reference statements)
0
23
0
Order By: Relevance
“…ALDH1A1 has frequently been described as a marker for stemness in human cancers ( 23 ), even though early investigations found it dispensable for stem cell function in murine hematopoietic and nervous systems ( 24 ). Studies on human glioblastoma cell lines suggested the enzyme as a mediator of TMZ resistance ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ALDH1A1 has frequently been described as a marker for stemness in human cancers ( 23 ), even though early investigations found it dispensable for stem cell function in murine hematopoietic and nervous systems ( 24 ). Studies on human glioblastoma cell lines suggested the enzyme as a mediator of TMZ resistance ( 25 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are drugs already available broadly inhibiting aldehyde dehydrogenases (e.g., disulfiram), which unfortunately can show severe side effects and toxicity ( 45 ). Isoform-specific inhibitors are under development ( 23 ), but their safety profile remain to be elucidated under the premise that ALDH1A1 is also expressed during development and in the adult brain ( 27, 46 ). We therefore approached the alternative, provided by the marked upregulation of pAKT in the target cells.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1 is lowly expressed in normal tissues and highly expressed in cancer the expression level of ALDH1is a marker that distinguishes normal stem cells from cancer stem cells. Clinical research studies have found that the prognostic ratio of the ALDH1 gene family can be used as a robust poor predictor of various solid cancers, including breast cancer, colon cancer, esophageal squamous cell carcinoma, non-small cell lung cancer, ovarian cancer, and other cancers ( 18 , 19 ). As a strong predictor, ALDH1 is also involved in deriving drug resistance in solid cancers.…”
Section: Aldh1 and Mechanismmentioning
confidence: 99%
“…The ALDH1A subfamily is also known to play an important role in embryogenesis and development by mediating retinoic acid signaling [ 8 ]. The ALDH1A1 gene codes a cytoplasmic enzyme and exerts vital physiological and pathophysiological functions, playing important roles in various chronic diseases, including cancer [ 9 ]. ALDH1A1 can induce cancer development via the maintenance of cancer stem cell properties, the modification of the metabolism, and the promotion of DNA repair.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of ALDH1A1, which acts as a tumor suppressor in certain cancers, is regulated by several epigenetic processes. Since the detoxification of ALDH1A1 often causes the failure of chemotherapy [ 9 ], ALDH1A1-targeted therapy has recently been widely used as a cancer chemotherapy [ 10 ], although the mechanism by which ALDH1A1 regulates carcinogenesis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%